The Digital Revolution of Islamic Entrepreneurship: A Study on Upholding the Principles of E-Commerce Legitimacy in Marketplaces - Pauzi Muhammad; Yoesi Primadiya Fitri; A Alak; Pidayan Sasnifa (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2024)
The rapid digital transformation in entrepreneurship has significantly influenced Islamic economic practices, particularly e-commerce. However, there is a lack of research focusing on methods to enforce e-commerce legitimacy in Islamic entrepreneurship. This study employs a qualitative library research approach with descriptive-analytical, conceptual, and philosophical methodologies. Secondary data is drawn from classical and contemporary fiqh muamalah texts, academic research, and digital resources. The data is analyzed systematically and normatively to explore key principles and methods for enforcing e-commerce legitimacy. The findings reveal six core principles essential for ensuring legitimacy in e-commerce: (1) mutual benefits for all parties, (2) mutual consent in transactions, (3) transparency in product and service information, (4) justice in avoiding any form of oppression, (5) excellent customer service, and (6) ethical behavior in business activities. These principles ensure compliance with Sharia and foster trust and fairness in digital marketplaces. The study concludes that enforcing e-commerce legitimacy principles is critical for addressing challenges in digital transactions and aligning them with Islamic entrepreneurial ethics. This contributes to prosperity (falah) for both sellers and buyers in worldly and spiritual contexts. Future research should focus on developing practical frameworks for applying these principles across various e-commerce platforms to enhance sustainability and compliance in the Islamic digital economy.Keywords: Digital Transformation, Islamic Entrepreneurship, E-Commerce Legitimacy, Sharia Compliance, Marketplace Ethics